City and Otherness: The Presence of Bolivians in the City of São Paulo - Bueno, Alexandre Marcelo (2023)
The city of São Paulo is known for its large number of immigrants in the past and in the present. These groups produce their presence in the public space, as is the case of Bolivian immigrants. This paper aims to examine some of these enunciative marks to decipher some of the meanings produced by immigrants in urban space. For this, I use the semiotics of Algirdas Julien Greimas and, mainly, the sociosemiotics of Eric Landowski. Thus, I hope to show how alterity is a constitutive part of urban space and think about some consequences of this manifestation of meaning for Brazilian society.